Gambaran Penggunaan Alat Pelindung Diri Dengan Gejala Ispa Pada Pekerja Penggilingan Padi Desa Waimital Dan Desa Waihatu - Ira Sandi Tunny (Pusat Riset dan Inovasi Nasional, 2022)
Personal Protective Equipment is a set of tools used by workers to protect all or part of their body from potentially dangerous work such as ISPA (Upper Respiratory Tract Infection) in rice mill workers in Waimital Village and Waihatu Village. The number of cases of ISPA each year in Indonesia is 150,000 cases or it could be said that someone dies every 5 minutes. The aim of this research was to determine the description of the use of personal protective equipment with symptoms of ISPA in rice mill workers in Waimital Village and Waihatu Village. This research method includes quantitative research with a descriptive approach. The sample in this research was 34 workers using total sampling. the majority of workers never use personal protective equipment as many as 20 people (58.8%), and the fewest are those who always use personal protective equipment as many as 3 people (8.8%). And 24 people (70.6%) experienced ISPA symptoms, while 10 people (29.4%) did not experience ISPA symptoms. It was concluded that on average workers did not use personal protective equipment, the majority of respondents experiencing ARI found in this study.